Characterization of dehalogenase for the degradation of 3-chloropropionic acid - Muslem, Wafaa Hassan (2017)
The use of herbicides that contain halogenated compounds, for example 3-chloropropionic acid (3-CP) poses significant environmental hazards as well as detrimental to human. The research detailed here investigated the isolation and identification of bacteria strains that could degrade 3-CP as its sole carbon source. Dehalogenase that can degrade 3-CP is rare in nature. In this study, two strains of dehalogenase producing bacteria capable of utilizing 3-CP were successfully isolated from abandoned agricultural land in Universiti Teknologi Malaysia. These bacteria were characterized by using 16S rRNA as well as biochemical analysis. Strain WH1 showed a 98 % sequence identity to Burkholderia cepacia with (accession number KU318403) whereas strain WH2 showed a 99% sequence identity to Bacillus cereus with (accession number KU721999). The results have shown that these bacteria were capable to grow in liquid minimal media supplied with 10 mM 3-CP as sole carbon source with doubling time of 43.62 h for WH1 and 14.75 h for WH2. Utilization of 3-CP was confirmed by detection of chloride ion released using halide ion assay technique for both strains which indicate their ability to degrade 3-CP. For further confirmation of 3-CP consumption, analysis by high performance liquid chromatography (HPLC) revealed that both B. cepacia WH1 and B. cereus WH2 effectively utilized ~100% of 10 mM 3-CP. This is the first report detailing both strains able to competently utilize 3-CP as their sole carbon source. Cell free extract of B. cereus strain WH2 was further characterized due to its faster growth on 3-CP compared to B. cepacia strain WH1. The intracellular dehalogenase from B. cereus WH2 was purified to homogeneity to afford a 2.5-fold (50 % yield) concentration with an estimated molecular mass of 37 kDa by SDS-PAGE analysis. Its highest enzyme activity was achieved at conditions of 30 oC and pH 7. While the activity of WH2 dehalogenase was substantially repressed by both Hg2+ and Ag2+, the enzyme was not inhibited by DTT and EDTA. Pertinently, kinetics evaluation revealed a higher affinity of the WH2 dehalogenase towards 3-CP than 3-chlorobutyric acid (3-CB), affording Km values of 0.32 mM (kcat 3.97 s-1) and 0.52 mM (kcat 4.35 s-1), respectively. The WH2 dehalogenase was ~1.6-fold catalytically more efficient (kcat/Km) in dehalogenating the three-carbon, 3-CP (12.4 mM-1 s-1) over the four-carbon, 3-CB (8.27 mM-1 s-1). From the data, it was identified that 3-CP degradation was not stimulated by co-factors, such as NAD+, NADH, NADP+, NADPH, FAD and CoA that did not affect the enzyme activity by demonstrating activities of <0.1 unite (g protein)-1. The amplified dehalogenase gene fragment was designated “deh-wh2” and subsequent analysis showed it belongs to Group II dehalogenase. Eight conserved residues that line the active site were identified: Asp10, Thr14, Ser117, Lys150, Tyr156, Ser174, Asn176 and Asp179. These residues are consistent with the residues found in the active site of DhlB, DehIVa and L-DEX. The product of 3-CP degradation was 3-hydroxypropionic acid based on HPLC. In conclusion, this study confirmed the presence of new dehalogenase isolated from various bacteria that have potential to utilize 3-CP, especially from contaminated environment.